Suppression of protein inactivation during freezing by minimizing pH changes using ionic cryoprotectants - Krausková, Ľubica; Procházková, Jitka; Klašková, Martina; Filipová, Lenka; Chaloupková, Radka; Malý, Stanislav; Damborský, Jiří; Heger, Dominik (International journal of pharmaceutics, 2016)
Freezing and lyophilization are often used for stabilization of biomolecules; however, this sometimes results in partial degradation and loss of biological function in these molecules. In this study we examined the effect of freezing-induced acidity changes on denaturation of the model enzyme haloalkane dehalogenase under various experimental conditions. The effective local pH of frozen solutions is shown to be the key causal factor in protein stability. To preserve the activity of frozen-thawed enzymes, acidity changes were prevented by the addition of an ionic cryoprotectant, a compound which counteracts pH changes during freezing due to selective incorporation of its ions into the ice. This approach resulted in complete recovery of enzyme activity after multiple freeze-thaw cycles. We propose the utilization of ionic cryoprotectants as a new and effective cryopreservation method in research laboratories as well as in industrial processes.
Keywords: roztoky; Cryopreservation; Freezing-induced pH shift; Protein cryopreservation; Hydrogen-Ion Concentration; Freezing stress; Protein aggregation; Freezing; Cryoprotective Agents; Buffers; Proteins; kryoprezervace; Solutions; Protein stability; proteiny; ionty; Freeze Drying; Ions; Freezing/thawing; Quality by design; zmrazování; lyofilizace; pufry; kryoprotektivní látky; koncentrace vodíkových iontů